Why Telecommuting Became Redundant During the COVID‐19 Pandemic? - , Wasantha Rajapakshe (Archives of Current Research International, 2021)
This paper reveals the facts that necessitated telecommuting in the 'new normal' virtual work environment. This is a cross-sectional study with a sample of executive-level employees working in the banking sector. Data were analyzed using the Pearson Product Moment Correlation Coefficient (PPMC). The findings reveal that the success of telecommuting during the COVID-19 pandemic depends on the nature of family responsibility, virtual work environment, virtual training, and self-management of the employees affected, while the work-life balance (WLB) is not significant. The decision-makers need to implement psychological training, skills-based training for managers, employees, and family members, and provide incentives to handle difficulties encountered in the pandemic situation. The present study proposes formulating a long-term policy that can successfully align with the new normal working conditions. This should encompass fundamental working rights under the virtual working environment, career development, and welfare of workers. To date, previous studies are based on the advantages of traditional telecommuting. However, this study considers employees’ perception of telecommuting in the COVID-19 pandemic; thus, the study fills the empirical gap in the research on telecommuting in the new normal working condition.